A Description of Acute Renal Failure and Nephrolithiasis Associated With Sodium–Glucose Co-Transporter 2 Inhibitor Use: A VigiBase Study - Frent, Ioana; Leucuta, Daniel; Bucsa, Camelia; Farcas, Andreea; Casoinic, Florin; Mogosan, Cristina (Frontiers in Pharmacology, 2022)
Background Food and Drug Administration issued a warning on the risk of acute kidney injury and a signal of neprolitiasis for patients using sodium glucose co-transporter 2 inhibitors (SGLT2i). We performed a descriptive analysis on acute renal failure (ARF) and nephrolithiasis cases reported to SGLT2i in the VigiBase®, in the scope of characterizing the patients and reactions, and to report on the disproportionality analysis. Methods We analyzed all ARF and nephrolithiasis reports for SGLT2i in VigiBase from inception up to September 2021. ARF cases were defined as reports containing at least one of the preferred terms (PTs) included in the ARF narrow Medical Dictionary for Regulatory Activities Standardised Queries (MedDRA SMQ). SGLT2i exposure was considered for reports with at least one gliflozin as suspected/ interacting drug. We characterized the patients, reporters, and reactions, and we present the proportional reporting ratio (PRR). Results Of 27,370,413 total reports in VigiBase, we found 3972 ARF reactions to gliflozins as suspected/ interacting drugs in 3751 patients and 231 nephrolithiasis reactions in 227 patients. The most cases were reported from the Americas (3057; 81.49%), for 45-64 years-of-age patients (1590; 59%). About 30% (1156) of the ARF reports were registered in 2018, most from spontaneous reporting, and from consumers followed by health care professionals (2235; 61% and 1440; 38%, respectively). Canagliflozin was the most involved gliflozin in the ARF and nephrolithiasis cases (2640; 67% and 109; 47%, respectively). The great majority of ARF and nephrolithiasis reports were serious (3761; 95% and 182; 79%, respectively). Of the total ARF cases reported, 51 had fatal outcome while 152 had not recovered/not resolved outcome. No fatal outcome was reported for nephrolithiasis. Disproportionality analysis in full database showed a PRR of 4.68 (95% CI 4.53–4.83) for all gliflozins-ARF and a PRR of 3.44 (95% CI 3.00–3.95) for all gliflozins-nephrolithiasis. Conclusions Most of ARF reports associated with gliflozins were serious, with an important number of cases with fatal outcome. A drug safety signal was found between ARF narrow SMQ and gliflozinsAlso, gliflozins were associated with an increase in the proportion of nephrolithiasis reports compared to other medications.